PENGENALAN HURUF, ANGKA DAN WARNA PADA ANAK USIA DINI MELALUI PEMBELAJARAN BERBASIS MULTI MEDIA - Fintri Indriyani; Kurniasih R Sihite (LPPM Universitas Bina Sarana Informatika, 2015)
Education given to the child at an early age is the basis of knowledge and thought processes in the future to teach toddler son on fundamental matters such as recognizing letters, numbers and colors need determination and patience from the teachers and parents. The basic concept of letters, numbers and colors important to learn as they learn the foundations of mathematics and science to solve problems absences ahead. During this study the letters, numbers and colors done by parents and teachers in schools with the help of tools such as card reading, books, and other props. With media activity is required from parents or teachers to attract children, sometimes even children get bored. Therefore, it is necessary that alternative media can be used as media for early childhood learning through interactive media are packaged in the form of animation is interesting, easy to understand and not boring fast. Educational applications as a learning medium to attract the attention of children to easily learn through play recognize letters, numbers and colors without problems limited the time and place.